A Brief Discussion on a Novel Method for Practical Date Measurement of Radiation Efficiency in Low-Frequency Communication Synchronization Antennas - Wenhao Li (The International Journal of Multiphysics, 2024)
With the continuous popularity of domestic radio watches and clocks, the importance of low-frequency radio stations has become increasingly significant. However, as domestic low-frequency radio stations have been established for over 20 years, with the erosion of time, radio antennas and ground networks have suffered varying degrees of damage, leading to a potential decline in the broadcasting efficiency of the radio stations. Especially in recent years, with the continuous development of technology, industries related to time accuracy have increasingly higher demands, surpassing the precision provided by traditional quartz clocks, which are no longer sufficient to meet market needs. To verify the actual transmission efficiency of existing low-frequency radio stations and to meet the demands of a wide range of radio users, this paper adopts a new testing method specifically designed for low-frequency communication signals for testing and analysis. Relevant parameters are organized, and communication data on the antenna parameters during the initial station construction period are collected and organized. The two sets of data are then analyzed and compared to validate the antenna efficiency of low-frequency stations' output signals. Based on the relevant verification data, the extent of damage to the low-frequency antenna ground network is determined, providing reference information for the subsequent repair of antennas and ground networks.